Development of a piezoelectric transducer coupling system for structural health monitoring applications - Giroto, Pedro Cerri [UNESP]; Viera, Martin Antonio Aulestia [UNESP]; Junior, Pedro Oliveira [UNESP]; Alexandre, Felipe Aparecido [UNESP]; Dotto, Fabio Romano [UNESP]; Gotz, Reinaldo [UNESP]; Lopes, Thiago Glissoi [UNESP]; Aguiar, Paulo Roberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Piezoelectric transducers have been widely used in structural health monitoring (SHM) frameworks. Recently, preliminary applications of these devices have emerged in the field of ultrasonic waves based on transmitter/receiver configuration. However, a practical problem has hindered its application to real-world structures due to the capacitive effect of the piezoelectric transducer. In other words, the transmitted chirp signal is not continuous in time domain due to losses in the signal amplitude. In addition, after applying fast Fourier transform (FFT) to this non-continuous time-domain signal, frequency losses are observed. Nevertheless, such frequencies are important for optimum sensitivity and coverage in damage detection. Owing to that, the goal of the present work was to design, implement, and test a coupling system, which will be used as a buffer to keep the amplitude of the chirp signal transmitted to the piezoelectric transducer. To achieve this, a series of simulations were performed for different electronic power supplies. At the end, the ± 12 V power supply was selected for the final prototype buffer coupling system. As a result, it was possible to keep the transmitted chirp signal amplitude as close to an ideal chirp signal as possible regarding to the chirp signal without buffer. The proposed system provides experience for future research of piezoelectric transducers and can be included in the calibration procedure of ultrasonic waves based on transmitter/receiver configuration for SHM applications.
Keywords: Automation; Buffer; Low cost system; Piezoelectric transducers; SHM